Sister in the Band of Brothers : Embedded with the 101st Airborne in Iraq - Skiba, Katherine M. (Book collections on Project MUSE., 2005)
"The risks were very real for her and anyone else who covered or fought in the war, even in its early days, long before triumph trailed off into something less than permanent victory. Her story testifies to the courage it took to endure such risks, while acknowledging the inevitable costs of war."--Jacket.